The Unknowing Side of the Algorithm: Decolonising live coding from Latin America. - Lara Mendoza, Aldo Mauricio; Zapata Cortés, Laura Viviana; Dündar, Emre (Organised Sound, 2023)
In this article we discuss and critically analyse some colonial assumptions of live coding from the Global North in contrast to the practice of live coding in Latin America (LATAM). To do so, we first look at different colonial problems that arise from different contemporary approaches. This results in a recommendation to consider more complex conditions of power that exist in the Global South and shows how live coding can put into practice greater complexity in the social system of art that could contribute to the structural reinforcement of the next society , as well as a critique of the inherited tonality in different media. We then proceed to criticise other sound colonial assumptions by using the decolonial praxis-theory from LATAM live coders and propose different forms of sound decolonisation. Finally, we propose a way to reconcile the convergence of interests between live coding in Latin America, the 'methodology' of Black studies, and the 'theory' of sonic fiction. In the conclusion, we pose several critical questions that could serve as the basis for further investigations.